An escrow-less identity-based group-key agreement protocol for dynamic peer groups. (22nd July 2009) - Chakrabarti, Saikat; Chandrasekhar, Santosh; Singhal, Mukesh
Dynamic Peer Group (DPG) applications, such as video-conferencing and multi-user gaming environments have proliferated the internet and group-key agreement protocols are critical in securing DPG communication. Identity-based cryptosystems avoid certificate management complications inherent to traditional public-key systems but introduce key escrow, which is highly undesirable in most applications. We design a scalable technique to eliminate key escrow and develop a distributed, escrow-less identity-based group-key agreement protocol for securing resource-constrained DPG communication. The proposed protocol is provably secure against passive adversaries, resilient to active attacks, scalable and more cost effective than any such protocol. We provide a detailed theoretical analysis to support the claims.